2020
DOI: 10.1007/s00508-020-01701-1
|View full text |Cite
|
Sign up to set email alerts
|

Nodular distribution pattern on chest computed tomography (CT) in patients diagnosed with nontuberculous mycobacteria (NTM) infections

Abstract: Informed consent: This is a retrospective study. For this type of study, formal consent is not required, because no personal data was contained and there is no concern about identifying information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…We observed that 72.3% of patients with bronchiectasis and NTM pulmonary disease had nonlobular central nodules on HRCT. Another study [ 39 ] evaluated the thoracic HRCT images of 63 patients with NTM infection and reported that 81% had nodules, 39.8% had lobular centrality, 11.6% had peripheral lymphatics, 9.5% had random distribution, and 20.6% had mixed. NTM are less pathogenic than tuberculous bacteria; hence, compared with tuberculosis, NTM pulmonary disease has fewer cavities [ 40 ] and thinner wall [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that 72.3% of patients with bronchiectasis and NTM pulmonary disease had nonlobular central nodules on HRCT. Another study [ 39 ] evaluated the thoracic HRCT images of 63 patients with NTM infection and reported that 81% had nodules, 39.8% had lobular centrality, 11.6% had peripheral lymphatics, 9.5% had random distribution, and 20.6% had mixed. NTM are less pathogenic than tuberculous bacteria; hence, compared with tuberculosis, NTM pulmonary disease has fewer cavities [ 40 ] and thinner wall [ 36 ].…”
Section: Discussionmentioning
confidence: 99%